Pollution of the Sea - Prevention and Compensation - Basedow, Jürgen.; Basedow, Jürgen.; Magnus, Ulrich.; Magnus, Ulrich. (Hamburg Studies on Maritime Affairs, International Max Planck Research School for Maritime Affairs at the University of Hamburg,, 2007)
In May 2005, the International Max Planck Research School for Maritime Affairs organized an international conference addressing marine pollution. At the conf- ence venue, the International Tribunal for the Law of the Sea, academics and practitioners debated recent developments from an interdisciplinary perspective. The papers shed light upon ecological aspects, upon the efforts of the international community to prevent and combat marine pollution by appropriate institutions and regulations, and upon the compensation of losses which have occurred despite those efforts. The present volume collects the papers of the conference and at the same time conveys an impression of the diversity of subjects discussed in the International Max Planck Research School for Maritime Affairs. The editors of this book have been supported by advice and help from several persons: In particular we are indebted to Dr. Silke Knaut and Dr. Anatol Dutta for their editorial assistance, to Anna-Maria Hubert who, as a native speaker, carried out the linguistic revision of several papers, and to Ingeborg Stahl for the prepa- tion of the manuscript. Hamburg, April 2007 Jürgen Basedow/Ulrich Magnus Contents Contributors...........................................................................................................IX Welcome Address and Introduction Marine Pollution as a Topic of Research and Policy Jürgen Basedow ......................................................................................................1.